Activating Vulnerable People into Good Jobs in Turkey - Finn, Dan; Grun, Rebekka; Herrera-Sosa, Katia; Immervoll, Herwig; Ridao-Cano, Cristobal; Uysal, Gokce; Yener, Ahmet Levent (World Bank, Washington, DC, 2015)
This report presents the results of a highly simplified profiling exercise to demonstrate the initial steps of profiling and draw some initial conclusions on the types of clients that might be covered by activation policies in Turkey, and the extent of their socio-economic vulnerability as well as labor market employability. A key conclusion is that policy makers will need to decide whether to put the emphasis on the former or on the latter so that the dual objectives of protecting the vulnerable and helping them move out of transfer dependence are achieved. The initial profiling exercise shows that several large subgroups of the vulnerable comprise inactive females, often with limited or outdated skills. A priority might be to rethink the offer of public services involved in up-skilling the workforce, such as lifelong learning, in order to mobilize the largest identified segments. This Executive Summary reflects on four connected background papers. A conceptual framework first defines vulnerability and activation policies. A second background paper takes stock of the progress of activation policies in Turkey to date. A third background paper profiles the large and diverse group of vulnerable people in Turkey into units of higher or lower priority, while the final background paper examines how the capacity and skills of the vulnerable, especially those in the high priority units, can be built.